STRATEGIES FOR THE PREVENTION AND CONTROL OF HYPERTENSION IN RURAL COMMUNITIES - Pedro do Valle Varela, João; Filipe Silva Oliveira, Luís; Coelho Soares Figueiredo, Luiz; Edas Corteletti Pereira Lopes, Victor; de Oliveira Figueiredo, Bruno; Ferraz Siliprandi, Laira; Teófilo da Silva, Kaicki; Djosci Coêlho de Sá, Henrique; Carlos Mendes Campos, Walter; Marcelo Pacheco Kokis, João (Health and Society, 2024)
Hypertension is a prevalent chronic condition that can lead to serious complications such as cardiovascular disease, stroke and kidney failure. The prevalence of hypertension is especially high in rural communities, where factors such as limited access to health care, lack of health information and socioeconomic conditions can contribute to a lack of control of the disease. Prevention and control strategies tailored to these communities are crucial to reducing the burden of hypertension and improving the overall health of the rural population. This brief explores effective strategies for the prevention and control of hypertension in rural communities, highlighting innovative approaches and associated challenges. The aim of this paper is to review and analyze strategies for the prevention and control of hypertension in rural communities. It aims to identify the main interventions that have proved effective, discuss approaches adapted to the needs and resources of rural communities, and address the challenges faced in implementing these strategies. This is a literature review, using qualitative and quantitative assumptions, using the PubMed, Scopus and Google Scholar databases. The health descriptors “Hypertension”, “Hypertension Management in Rural Areas”, “Telemedicine”, “Community Interventions” and “Rural Health Policies” were used to refine the research. The time frame covers the years 2018 to 2022. The focus is to promote a comprehensive understanding of best practices and areas that need more attention to improve the management of hypertension in rural contexts. Preventing and controlling hypertension in rural communities requires a multifaceted approach that takes into account the particularities of these areas, including barriers to accessing healthcare, resource limitations and specific cultural needs. Education is key to preventing hypertension. Awareness programs about risk factors, the importance of regular blood pressure monitoring and lifestyle changes can have a significant impact. Community initiatives such as workshops, lectures and local media campaigns can help raise awareness of hypertension and promote healthy habits. Improving access to healthcare is crucial for hypertension control in rural areas. This can include the implementation of mobile health units, telemedicine and partnerships with health organizations to provide regular medical services and blood pressure monitoring. Community screening programs and regular consultations can help identify and treat cases of hypertension early. Interventions that encourage a healthy diet, rich in fruit, vegetables and low in sodium, as well as regular physical activity, are essential for the prevention and control of hypertension. Nutritional education programs and the promotion of community physical activities, such as walking groups or sports, can be effective in promoting a healthy lifestyle. Thus, many people with hypertension also have other health conditions, such as diabetes or obesity. Integrated strategies that address hypertension alongside other health conditions can improve overall outcomes. This includes chronic disease management programs that provide support for managing multiple health conditions simultaneously. Involving the community in the planning and implementation of prevention and control strategies can increase the acceptance and effectiveness of interventions. Community groups, local leaders and non-governmental organizations can play an important role in promoting health programs and mobilizing resources. The effective implementation of hypertension control strategies in rural communities faces several challenges. Barriers can include a lack of adequate health infrastructure, a shortage of health professionals, limited access to medicines and treatments, and cultural factors that can affect the acceptance of interventions. In addition, logistical and financial difficulties can limit the ability to implement and maintain health programs in remote areas. Therefore, the approach to preventing and controlling hypertension in rural communities must be adapted to the specific needs and characteristics of these areas. Effective strategies include community education and awareness, improving access to health care, promoting a healthy lifestyle and integrated management of comorbidities. Involving the community and overcoming challenges related to infrastructure and resources are critical aspects for the success of these strategies. With a multifaceted and collaborative approach, it is possible to reduce the prevalence and impact of hypertension in rural communities, promoting better health and an improved quality of life for their inhabitants.